A palaeoenvironmental context for Terminal Upper Palaeolithic and Mesolithic activity in the Colne Valley: Offsite records contemporary with occupation at Three Ways Wharf, Uxbridge. (June 2014) - Grant, Michael J.; Stevens, Chris J.; Whitehouse, Nicki J.; Norcott, David; Macphail, Richard I.; Langdon, Catherine; Cameron, Nigel; Barnett, Catherine; Langdon, Peter G.; Crowder, John; Mulhall, Nicola; Attree, Kevin; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Multi-proxy analyses from floodplain deposits in the Colne Valley, southern England, have provided a palaeoenvironmental context for the immediately adjacent Terminal Upper Palaeolithic and Early Mesolithic site of Three Ways Wharf. These deposits show the transition from an open cool environment to fully developed heterogeneous floodplain vegetation during the Early Mesolithic. Several distinct phases of burning are shown to have occurred that are chronologically contemporary with the local archaeological record. The floodplain itself is shown to have supported a number of rare Urwaldrelikt insect species implying human manipulation of the floodplain at this time must have been limited or episodic. By the Late Mesolithic a reed-sedge swamp had developed across much of the floodplain, within which repeated burning of the in situ vegetation took place. This indicates deliberate land management practices utilising fire, comparable with findings from other floodplain sequences in southern Britain. With similar sedimentary sequences known to exist across the Colne Valley, often closely associated with contemporary archaeology, the potential for placing the archaeological record within a spatially explicit palaeoenvironmental context is great.